2018
DOI: 10.1016/j.commatsci.2017.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and pitfalls of density functional perturbation theory phonons calculations from a high-throughput perspective

Abstract: The diffusion of large databases collecting different kind of material properties from highthroughput density functional theory calculations has opened new paths in the study of materials science thanks to data mining and machine learning techniques. Phonon calculations have already been employed successfully to predict materials properties and interpret experimental data, e.g. phase stability, ferroelectricity and Raman spectra, so their availability for a large set of materials will further increase the anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…We have also observed 26 that the presence of small negative frequencies for the acoustic phonon frequencies in the close proximity of the Γ point could be associated with poor choices of the k or q point grids. In particular, we have observed that these are hardly ever a signal of a real incommensurate instability.…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…We have also observed 26 that the presence of small negative frequencies for the acoustic phonon frequencies in the close proximity of the Γ point could be associated with poor choices of the k or q point grids. In particular, we have observed that these are hardly ever a signal of a real incommensurate instability.…”
Section: Methodsmentioning
confidence: 85%
“…The Brillouin zone has been sampled using equivalent k -point and q -point grids that respect the symmetries of the crystal and with a density of approximately 1500 points per reciprocal atom, as suggested in ref. 26 . The q -point grid is always Γ-centered.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The exchange-correlation functional was described using the PBEsol [42] approximation, that has proven to provide accurate phonon frequencies compared to experimental data [19]. Norm-conserving pseudopotentials [17] extracted from the Pseudodojo pseudopotentials table version 0.3 [61] were used for all the elements and the Brillouin zone was sampled with 8 × 8 × 5 Monkhorst-Pack grids [35], [43]. Due to standard DFT's known limitations in describing the band gap, we limit our analysis to Mg 3 Sb 2 , CaMg 2 Sb 2 and CaMg 2 Bi 2 , Fig.…”
Section: Calculation Detailsmentioning
confidence: 99%